“Executive functions” cannot be distinguished from general intelligence: two variations on a single theme within a symphony of latent variance - Royall, Donald R.; Palmer, Raymond F. (Frontiers in Behavioral Neuroscience, 2014)
The empirical foundation of executive control function (ECF) remains controversial. We have employed structural equation models (SEM) to explicitly distinguish domain-specific variance in ECF performance from memory (MEM) and shared cognitive performance variance, i.e., Spearman’s “g”. ECF does not survive adjustment for both MEM and g in a well fitting model of data obtained from non-demented older persons (N = 193). Instead, the variance in putative ECF measures is attributable only to g, and related to functional status only through a fraction of that construct (i.e., dECF). dECF is a homolog of the latent variable δ, which we have previously associated specifically with the Default Mode Network (DMN). These findings undermine the validity of ECF and its putative association with the frontal lobe. ECF may have no existence independent of general intelligence, and no functionally salient association with the frontal lobe outside of that structure’s contribution to the DMN.